Three new species of the Old World Oedemeridae (Coleoptera) - Švihla, Vladimír (Zootaxa, 2008)
New species of the family Oedemeridae are described and illustrated: Ditylus catenulatus sp. nov. (China: Sichuan), Chrysanthia kantneri sp. nov. (India: Maharasthra) and Colobostomus kenyaensis sp. nov. (Kenya). The male of Indasclera akiyamai Švihla, 1997 is described and illustrated and this species is newly recorded from Laos.